ҚАЗАҚ ТІЛІНДЕГІ МАТА ТҮРЛЕРІ АТАУЛАРЫНЫҢ ЖАСАЛУ ЕРЕКШЕЛІКТЕРІ (Алматы технологиялық университетінің хабаршысы, 2021)
In the submitted article are revealed features of word formation of the name of types of fabrics, which practical use has made a huge contribution to development of a lexicon of Kazakh and are considered as the main part of the history, culture, customs and traditions for the first time and the scientific novelty consists in it. Kazakh language word have been fully accepted since ancient times, as well as the main methods of them are as follows: 1) synthetic (morphology), 2) analytical (syntax), 3) lexical and semantic approaches. With the help of these methods, we determine the peculiarities of their word-formation in the Kazakh language, which facilitates the easy assimilation of the names of fabrics at practical classes of the professional Kazakh language.